Actualizing the Concept of Ar-Rusyd in the Exegesis of Surah An-Nisa' (5-6) as a Model for Youth Character Education - Hanif, Rifqi Maulana; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2025)
This study aims to examine classical and contemporary interpretations of Surah An-Nisā’ verses 5-6, with a focus on the concept of ar rusyd and its relevance to the formation of social responsibility and youth character education. This study is motivated by differences in exegetical approaches that tend to limit ar-rusyd to intellectual competence and financial management in classical interpretations, alongside contemporary efforts to expand its meaning to encompass moral and social dimensions. This research employs a qualitative method using a library research approach, through comparative analysis of classical tafsir literature and relevant contemporary studies. The findings indicate that ar-rusyd does not merely represent intellectual maturity but also includes moral maturity, clarity of reasoning, and social readiness in carrying trust (amanah) and responsibility. Contemporary interpretations emphasize that the concept of ar rusyd is consistent with the principles of justice and equality that constitute the fundamental values of the Qur’an and cannot be used as a justification for discriminatory hierarchical relations. Furthermore, this study finds that ar-rusyd, together with the values of amanah and nafs, can serve as a conceptual foundation for developing a Qur'an-based model of youth character education. In conclusion, the actualization of the concept of ar-rusyd makes a significant contribution to strengthening thematic Qur'anic exegesis and advancing Islamic education oriented toward the formation of mature, just, and responsible character.